Interfacial reactions between sapphire and Ag–Cu–Ti-based active braze alloys. (15th January 2016) - Ali, Majed; Knowles, Kevin M.; Mallinson, Phillip M.; Fernie, John A.
Abstract: The interfacial reactions between two commercially available Ag–Cu–Ti-based active braze alloys and sapphire have been studied. In separate experiments, Ag–35.3Cu–1.8Ti wt.% and Ag–26.7Cu–4.5Ti wt.% alloys have been sandwiched between pieces of R-plane orientated sapphire and heated in argon to temperatures between 750 and 900 °C for 1 min. The phases at the Ag–Cu–Ti/sapphire interfaces have been studied using selected area electron diffraction, energy dispersive X-ray spectroscopy and electron energy loss spectroscopy. Gradual and subtle changes at the Ag–Cu–Ti/sapphire interfaces were observed as a function of temperature, along with the formation of a transient phase that permitted wetting of the sapphire. Unequivocal evidence is shown that when the active braze alloys melt, titanium first migrates to the sapphire and reacts to dissolve up to ∼33 at.% oxygen, forming a nanometre-size polycrystalline layer with a chemical composition of Ti2 O1–x (x ≪ 1). Ti3 Cu3 O particles subsequently nucleate behind the Ti2 O1–x layer and grow to become a continuous micrometre-size layer, replacing the Ti2 O1–x layer. Finally at 845 °C, a nanometre-size γ-TiO layer forms on the sapphire to leave a typical interfacial structure of Ag–Cu/Ti3 Cu3 O/γ-TiO/sapphire consistent with that seen in samples of polycrystalline alumina joined to itself with these active braze alloys. These experimental observations have been used to establish a definitive bonding mechanism for the joining of sapphire with Ag–Cu alloys activated by small amounts of titanium. Graphical abstract: